1999
DOI: 10.1524/ract.1999.85.34.97
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Extraction of Plutonium(VI) by Tri n-Amyl Phosphate

Abstract: Plutonium(VI) / Solvent extraction / Enthalpy of extraction / Tri n-amyl phosphate SummaryThe effect of temperature on the extraction of plutoniuni(VI) by tri n-amyl phosphate (TAP) from nitric acid media has been studied and the results are reported here. The enthalpies for the extraction derived from the distribution ratios are found to be exothermic, like the enthalpies of extraction of Pu(VI) by tri nbutyl phosphate (TBP). Attempts have been raade to evaluate the free energy change, the entropy change and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…It was observed that the extraction of U(VI) and Th(IV) decreased with increase in temperature, suggesting the exothermic nature of the extraction equilibria. Similar observations have been reported for the extraction of U and Pu with solvating organophos- phorus extractants like tri-n-butyl phosphate (TBP), trin-amyl phosphate (TAP), sulphoxides like di-2-ethylhexyl sulphoxide (DEHSO) and amides like dihexyl hexanamide (DHHA) [19][20][21][22][23][24]. Due to very low D Th values (≤ 10 −3 ) at 3 M HNO 3 , the extraction experiments could not be carried out in the case of D2EHIBA and D2EHPVA.…”
Section: Effect Of Temperature On Distribution Of U(vi) and Th(iv)supporting
confidence: 72%
“…It was observed that the extraction of U(VI) and Th(IV) decreased with increase in temperature, suggesting the exothermic nature of the extraction equilibria. Similar observations have been reported for the extraction of U and Pu with solvating organophos- phorus extractants like tri-n-butyl phosphate (TBP), trin-amyl phosphate (TAP), sulphoxides like di-2-ethylhexyl sulphoxide (DEHSO) and amides like dihexyl hexanamide (DHHA) [19][20][21][22][23][24]. Due to very low D Th values (≤ 10 −3 ) at 3 M HNO 3 , the extraction experiments could not be carried out in the case of D2EHIBA and D2EHPVA.…”
Section: Effect Of Temperature On Distribution Of U(vi) and Th(iv)supporting
confidence: 72%